2009
DOI: 10.4049/jimmunol.0900550
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Complement in the Enhanced Susceptibility of Steatotic Livers to Ischemia and Reperfusion Injury

Abstract: Hepatic steatosis typically renders the donor organ unusable, as donor organs with >30% steatosis are more likely to develop graft failure. The mechanisms leading to failure are not well defined, but steatosis enhances hepatic susceptibility to ischemia reperfusion injury (IRI). We investigated the role of complement in hepatic IRI in lean and steatotic (diet-induced) mice. Steatotic mice were significantly more susceptible to total warm hepatic IRI than lean mice as determined by serum alanine aminotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 52 publications
(44 reference statements)
5
39
0
Order By: Relevance
“…This result further suggests that complement such as C3a, C5a, and MAC may play a critical role in hepatic IRI in liver transplantation. These results are consistent with findings reported by He et al 24 It is well established that C3a and C5a bind with high affinity to the C5a receptor (C5aR) on polymorphonuclear leukocytes, monocytes, and macrophages 29 to stimulate oxidative metabolism and the production of reactive oxygen species in neutrophils and T cells, thereby leading to the amplification of inflammatory responses. 65,66 It is worth noting that we did not have any primary reasons to select AST instead of ALT as a main parameter for the detection of the degree of liver injury in our experiments.…”
Section: Cd59 and Complement Insupporting
confidence: 93%
See 1 more Smart Citation
“…This result further suggests that complement such as C3a, C5a, and MAC may play a critical role in hepatic IRI in liver transplantation. These results are consistent with findings reported by He et al 24 It is well established that C3a and C5a bind with high affinity to the C5a receptor (C5aR) on polymorphonuclear leukocytes, monocytes, and macrophages 29 to stimulate oxidative metabolism and the production of reactive oxygen species in neutrophils and T cells, thereby leading to the amplification of inflammatory responses. 65,66 It is worth noting that we did not have any primary reasons to select AST instead of ALT as a main parameter for the detection of the degree of liver injury in our experiments.…”
Section: Cd59 and Complement Insupporting
confidence: 93%
“…20 -22 Experimental and clinical evidence indicates that IR triggers complement activation in several organs. 23 Recently, using a novel inhibitor CR2-Crry to inhibit MAC formation and C3 activation at the site of complement activation, He et al 24 demonstrated that an enhanced susceptibility to IRI of steatotic livers was associated with complement activation in a mouse model. Additionally, C6 deficiency in rats protects against ischemia damage in rat orthotopic liver transplantation (OLT) recipients, which indicates the role of MAC in the pathogenesis of hepatic IRI.…”
mentioning
confidence: 99%
“…Strategies to limit hepatic ischemic/reperfusion injury in both obese and non-obese patients are clearly important but may be of greatest utility in those with steatosis. Steatosis may portend a greater risk for ischemia-reperfusion injury, 26,27 which has led to broader basic efforts to further understand this theory. Further understanding of this relationship will have important clinical implications in hepatic surgery and transplantation, and the assessment of patient risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from several studies has suggested that the complement system is involved in the pathogenesis of a variety of liver disorders, including liver fibrosis, viral hepatitis, alcoholic liver disease and hepatic ischemia/reperfusion injury (IRI) [12][16]. In these disease settings, complement activation products promote tissue inflammation and injury, particularly via the generation of the complement activation products C3a and C5a, which promote inflammation via direct and indirect mechanisms by interacting with their receptors [17][19].…”
Section: Introductionmentioning
confidence: 99%